Family study of the major histocompatibility complex in patients with systemic lupus erythematosus: importance of null alleles of C4A and C4B in determining disease susceptibility. Issue 6363 (5th February 1983) - Fielder, A H; Walport, M J; Batchelor, J R; Rynes, R I; Black, C M; Dodi, I A; Hughes, G R
Abstract : The families of 29 patients with systemic lupus erythematosus and 42 normal subjects were studied to determine the inheritance of the HLA-A, B, C, and DR antigens and also the complement polymorphisms for C2, C4A, C4B, and Bf, which are encoded in the same region of the sixth chromosome. Null (silent) alleles for C4A, C4B, or C2 were found in 24 of the 29 (83%) patients compared with 18 of the 42 (43%) normal controls. HLA-DR3 was present in 20 (69%) of the patients and seven out of 39 (18%) of the normal controls. There was strong linkage disequilibrium between DR3 and the null alleles for C4A and C4B. The data did not permit the relative contributions of DR3 and null factors of C4A and C4B as genetic risk factors to be distinguished. The known association of systemic lupus erythematosus with uncommon inherited and acquired deficiencies of complement components suggests, however, that the presence of null alleles for C4A and C4B, as well as C2, found in most of the patients, is relevant to their genetic susceptibility to this disease.